PATIENT SATISFACTION REGARDING NURSING CARE IN THE NEUROSURGERY WARD IN TERTIARY CARE HOSPITAL, PUNJAB, PAKISTAN - Saima Khadim; Sana; Shaista Younas; Adeela Qayyum (International Journal of Contemporary Issues in Social Sciences, 2024)
Background: Specialized nursing care is crucial for hospitalized patients in neurological units. An essential metric for assessing the standard of nursing work is patient satisfaction with the level of care received. Patients are regarded as valuable resources. For evaluating the standard of nursing care in particular as well as the general quality of hospital services. Objective: Assess the level of satisfaction hospitalized patients has with the quality of nursing care provided in the neurological wards. Methods: The current study was a cross-sectional research. Targeted was a purposeful sample of 131 hospitalized patients who fulfilled the inclusion criteria for the study and were admitted in the neurological ward of the Teaching Hospital. The data starting on December 21, 2021, and ending on February 1, 2022, was collecting. In-person interviews were employed to gather data. The degree of their satisfaction with the level of nursing care was assessed using the Patient Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ). Results: Eighty-five percent (88.5%) of the survey participants expressed dissatisfaction with the standard of nursing care they received in the neurological wards. Additionally, 11.5% expressed some degree of satisfaction with the standard of nursing care they received. Conclusion: Most patients expressed dissatisfaction with the standard of nursing care received. This indicates a significant gap that has to be filled quickly and effectively.